Immune regulation and clinical response of Chinese herbal injections combined with TACE in hepatocellular carcinoma: a cumulative logit regression and Bayesian network meta-analysis - Wenjuan Gu; Tianyu Zhu; Yujuan Zhang; Ming Xue; Qingfeng Liu (Frontiers in Medicine)
ObjectivesThis study evaluated the immunomodulatory effects and clinical efficacy of Chinese herbal injections (CHIs) combined with transcatheter arterial chemoembolization (TACE) in hepatocellular carcinoma (HCC) patients using cumulative logit regression and Bayesian network meta-analysis.MethodsA systematic review of 48 randomized controlled trials (RCTs) involving 4,293 HCC patients was conducted using PubMed, Cochrane Library, EMBASE, Scopus, and Google Scholar. Outcomes included immune markers (CD3+, CD4+, CD8+, CD4+/CD8+ ratio, and NK cells), clinical response rate, and overall survival (6-month, 1-year, and 2-year). Cumulative logit regression and Bayesian network meta-analysis were applied to synthesize ordinal and continuous outcomes.ResultsCompared to TACE alone, Aidi, Compound Kushen, and Huachansu significantly enhanced the immune function. Aidi increased CD3+ T cells (MD = 10.95, 95% CI: 8.04–13.86), CD4+ T cells (MD = 7.13, 4.37–9.89), CD4+/CD8+ ratio (MD = 0.31, 0.20–0.41), and NK cells (MD = 6.30, 4.49–8.12), while Compound Kushen showed the highest CD4+/CD8+ improvement (MD = 0.47, 0.37–0.56) and NK cell elevation (MD = 9.11, 7.32–10.91). Huachansu increased CD3+ T cells (MD = 8.74, 4.43–13.06) and CD4+ T cells (MD = 8.00, 4.21–11.80). For clinical outcomes, Compound Kushen (HR = 2.57, 1.9–3.59) and Aidi (HR = 2.28, 1.68–3.18) improved clinical response rates versus TACE. Aidi enhanced 6-month (OR = 2.57, 1.44–4.56) and 1-year survival (OR = 2.46, 1.56–3.88), whereas Huachansu (OR = 3.47, 2.42–4.97) and Compound Kushen (OR = 2.91, 1.07–7.89) improved 2-year survival.ConclusionAidi, Compound Kushen, and Huachansu enhance immune function and survival in HCC patients when combined with TACE. Compound Kushen showed the most significant immunomodulatory effects, while Aidi and Huachansu improved short- and long-term survival, respectively. Further high-quality head-to-head RCTs are required to validate these results.